AgI cryptates of N,N′-bridged 1,10-diazacyclooctadeca-5,14-diynes: a comparison between the complexes and the free ligands - Gleiter, Rolf; Hirschheydt, Thomas von; Rominger, Frank (European journal of inorganic chemistry, 2000)
The bicyclic diaza alkynes 1−3 react quantitatively with silver triflate to give the corresponding cryptates 4−6. The solid-state structures of the silver(I) complexes 4 and 6 were determined by means of X-ray diffraction studies. A comparison of the molecular structures of 4 and 6 with those of the uncomplexed ligands 1 and 3 reveals drastic changes in the conformations of the ligands. Evidence for an interaction of the silver ions with alkyne units in 4 and 6 was found from a high-field shift of the 13C signal for the sp carbons in the 13C NMR spectrum.